Characterization and in vitro release kinetics of chitosan based biocomposites from Scotch Bonnets - BİLĞİÇ ALKAYA, DİLEK; AYAZ SEYHAN, SERAP (My University, 2022)
© 2022 Indian Chemical SocietyThe main aim of this study is to formulate the combination of the bioactive composite containing chitosan/β -tricalcium phosphate (CH/β-TCP) as potential drug delivery platforms for the sustained release of antibiotics. Herein the mode of amoxicillin (AMX) maintained in the β-TCP/chitosan composite was characterized using XRD, FT-IR to confirm the phase purity and functional groups. SEM was used to examine the size and shape of particles. The SEM images of the biocomposites after drug release confirmed that they are biodegradable. In vitro drug release experiments in PBS (pH 7.4) revealed a sustained release profile in a neutral medium. Drug release profiles were evaluated according to five different kinetic models including Zero Order, First Order, Higuchi, Hixon Crowel, and Korsmeyer-Peppas. The release profile was best expressed by the Korsmeyer Peppas model because the results showed high linearity. Overall, the positive effect of chitosan coating on the drug elution profile of β-TCP as carriers for the controlled delivery of antibiotics was regarded as biocompatible for the controlled drug delivery system.
Keywords: Yaşam Bilimleri; Moleküler Biyoloji ve Genetik; Sitogenetik; Kimya; Biyokimya; Biyoinorganik Kimya; Fizikokimya; Elektrokimya; İnorganik Kimya; Temel Bilimler; Life Sciences; Molecular Biology and Genetics; Cytogenetic; Chemistry; Biochemistry; Bioinorganic Chemistry; Physical Chemistry; Electrochemistry; Inorganic Chemistry; Natural Sciences; Temel Bilimler (SCI); Yaşam Bilimleri (LIFE); KİMYA, İNORGANİK VE NÜKLEER; ELEKTROKİMYA; KİMYA, FİZİKSEL; KİMYA, ORGANİK; BİYOKİMYA VE MOLEKÜLER BİYOLOJİ; Natural Sciences (SCI); Life Sciences (LIFE); CHEMISTRY; MOLECULAR BIOLOGY & GENETICS; CHEMISTRY, INORGANIC & NUCLEAR; ELECTROCHEMISTRY; CHEMISTRY, PHYSICAL; CHEMISTRY, ORGANIC; BIOCHEMISTRY & MOLECULAR BIOLOGY; İlaç Keşfi; Fiziksel ve Teorik Kimya; Fizik Bilimleri; Organik Kimya; İnorganik kimya; Drug Discovery; Physical and Theoretical Chemistry; Physical Sciences; Organic Chemistry; Amoxicillin; Chitosan; Drug delivery; TCP